Effect of water extracts of some plants on growth of some skin fungi - Noor ALhuda Q. Fadeel , Amnh k. Saber (Journal of Pure & Applied Sciences, 2019)
This paper aims to study the inhibitory activity of clove extracts, pomegranate peels, chamomile, pepper and bitter melon by digging on a number of dermatophytes including Trichophyton, Microsporum spp, Mucor, Aspergillus Niger, the results showed that the most isolated strains of skin fungi were Microsporum (53.84%), followed by Trichophyton (30.76%). Aspergillus Niger and Mucor were isolated from toes infected with fungus, a non-cutaneous opportunistic fungus. Most aquatic extracts of the studied plants showed high inhibition efficiency on isolated fungi and increased inhibition with increasing concentration of treated plant extract. The water extract of clove inhibited the growth of all tested fungi, which affected the treated fungi (75%), compared with the water extract of bitter melon and chamomile (50%) and water extract of pomegranate and pepper (25%). The results revealed that water extracts of chamomile, pepper and pomegranate husks stimulated the growth of Trichophyton spp mushrooms and intensely. While the fungus Mucor spp showed its high resistance (100%) against all extracts treated even with increasing concentrations used. The highest inhibition rate was inhibited Microsporum (50.044 mm) at concentration (0.58ppm) with chamomile water extract. While the results of statistical analysis showed that there were significant differences between the extracts of the studied plants in their effect on fungi, especially the fungus Microsporum and Trichophyton water extract of cloves were not significant in other.